Resilient Routing for SDM-EON as a Crucial Enabler for the New Traffic Generation - Lopes, Rafael S.; Oliveira, Helder M. N. S. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2023)
The introduction of new technologies and applications connected to the Internet has demonstrated the inability of current photonic networks to provide resources for the next-generation Internet. One of the main proposals to deal with this problem today is space-division multiplexing elastic optical networks. However, to transport the massive amount of data that is being generated today, these backbone networks should provide efficient resilience mechanisms. In this way, this Course Completion Work contributes efficient and reliable solutions to meet the future rapid growth of Internet traffic. The proposed solutions were extensively compared with related work on performance measurement metrics. The evaluation results show that the proposed solutions are efficient, boosting the latest generation optical networks.